The Influence of Social Media Marketing Activities on Customer Satisfaction and Participation Intention in Oriflame Multi-Level Marketing (Mlm) - Hasdiansa, Ilma Wulansari (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
This study investigates the impact of social media marketing activities on customer satisfaction within Oriflame’s customer base, with a focus on the mediating roles of social identification and perceived value. The growing prominence of social media has transformed how businesses engage with consumers, making it critical to utilize these platforms effectively. Using Structural Equation Modeling (SEM), this research analyzes data from 50 respondents in Makassar City, collected through structured questionnaires. The findings reveal that social media marketing—through engaging content, interactive communication, and personalized efforts—positively influences customer satisfaction. Furthermore, satisfaction significantly drives key behavioral intentions: participation, purchasing, and willingness to join Oriflame’s multilevel marketing (MLM) network. The study highlights the importance of customer satisfaction as a predictor of loyalty and advocacy behavior, which are essential for sustained competitive advantage. Social identification and perceived value serve as significant mediators in this relationship. Social identification enhances emotional connection and a sense of belonging to the brand community, while perceived value reflects the alignment between customer expectations and the brand’s offerings, enriching the customer experience. These mediating factors strengthen the influence of social media marketing on satisfaction. The research offers practical insights for businesses aiming to enhance their digital marketing strategies. It underscores the necessity of fostering meaningful interactions on social media to boost not only satisfaction but also long-term engagement and conversion. By understanding these dynamics, companies like Oriflame can optimize marketing efforts, build stronger customer relationships, and achieve sustained growth in the digital era.